2021
DOI: 10.3906/elk-2003-12
|View full text |Cite
|
Sign up to set email alerts
|

A multiple sensor fusion based drift compensation algorithm for mecanum wheeled mobile robots

Abstract: This paper investigates a multiple sensor fusion based drift compensation technique for a mecanum wheeled mobile robot platform. The mobile robot is equipped with high precision encoders integrated to the wheels and four accelerometers placed on its chassis. The proposed algorithm combines the information from the encoders and the acceleration sensors to estimate the total drift in the acceleration dimension. The inner loop controller is designed utilizing a disturbance observer based acceleration control stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This technique combined information from encoders and acceleration sensors to estimate drift in the acceleration dimension. Experimental results demonstrated the effectiveness of this method in reducing the localization drift of wheeled robots [ 10 ]. T. Huang et al found that visual semantic fusion is a key technology for understanding autonomous driving scenes, and its accuracy is affected by changes in lighting.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique combined information from encoders and acceleration sensors to estimate drift in the acceleration dimension. Experimental results demonstrated the effectiveness of this method in reducing the localization drift of wheeled robots [ 10 ]. T. Huang et al found that visual semantic fusion is a key technology for understanding autonomous driving scenes, and its accuracy is affected by changes in lighting.…”
Section: Related Workmentioning
confidence: 99%
“…In Eq (10), there are the Mahalanobis distance measurement error terms for visual, IMU, and encoder, respectively, representing the marginalization term. H is the total number of maps for the Kth frame, P is the Huber robust kernel function, and E, EI, and EG are the noise covariance matrices for visual, IMU, and encoder, respectively, representing the state variables.…”
Section: Plos Onementioning
confidence: 99%
“…The system's input is the robot speed error with variation, and the system's output is 8-bit pulse width modulation translated to fuzzy forms. Later research focused on robots with additional sensing systems to construct autonomous guidance systems to maneuver a wheeled mobile robot securely in its surroundings (Alhalabi et al, 2021). Guzel and Bicker (2011) described obstacle avoidance methods based on vision.…”
Section: Introduction and Related Workmentioning
confidence: 99%